(3OhQ GdHfc cCejf GSJKeGQs - (3eMeO Jhajb(B, (3SYhOjs ((3GdbGgQI(B:s (3OGQ GdCejf ddfTQ hGdJhRjY(B,s, 2002)
(3GdhXGFa GdJbdjOjI ddHfhc GdJLGQjI(B-(3GdhOGFY GdfbOjI(B-(3YbO GdhOjYI GdeUQajI(B-(3aJM MSGH GdhOGFY GdeUQajI(B-(3JYQja Gdfbd GdeUQaj(B-(3GdMSGH GdLGQj(B-(3JYQja GdMSGH GdLGQj hNUGFUg hTQhWg(B-(3GdBKGQ GdJj JJQJH Ydi GdMSGH GdLGQj hcjajI EbaGdg(B-(3GdEYJeGOGJ GdeUQajI(B-(3GdNOeGJ GdeUQajI(B-(3JWhQ fXGe CefGA GdGSJKeGQ(B-(3OhQ GdHfhc GdJLQjI aj EOGQI CehGd GdYedGA hGdNOeGJ GdeQJHWI HgG(B-(3EOGQI GdHc ddCehGd hGdeeJdcGJ ddYedGA MGd MjGJge(B-(3EOGQI CehGd heeJdcGJ GdYedGA HYO haGJge(B-(3Jchjf hEOGQI eMGaX GdChQGb GdeGdjI(B-(3Jchjf eMaXI GdChQGb GdeGdjI HeYQaI GdHfc(B-(3EOGQI GdHfc cCejf GSJKeGQ deMGaX GdChQGb GdeGdjI(B-(3GdWHjYI GdbGfhfjI dOhQ GdHfc GdJLGQj cCejf GSJKeGQ(B-(3ehba Gdabg hGdJTQjY GdebGQfMhd gPg GdWHjYI(B-(3eSFhdjI GdHfc cCejf GSJKeGQs
(3HHdjhZQGajG(B: (3U(B.115s
Keywords: (3GdHfhc GdJLGQjIs; (3GdeGdjIs; (3Hfhc GdESJKeGQs